Shielding assessment of high field (QED) experiments at the ELI-NP 10 PW laser system. (24th January 2017) - Popovici, M A; Mitu, I O; Căta-Danil, Gh; Negoiţă, F; Ivan, C
Abstract: High field quantum electrodynamics experiments will be conducted in the E6 experimental area of the Extreme Light Infrastructure-Nuclear Physics building. Here electrons and protons will be accelerated up to relativistic energies by multi-petawatt laser beam—target interactions. In this respect, the requirements for radiological safety measures are similar to those associated with the operation of conventional high energy accelerators. The paper presents a FLUKA simulation approach to the shielding assessment of the individual experiments. Updated source terms were used in order to compute ambient dose equivalent rates throughout E6 and neighbouring areas and check the compliance of the results with legal dose constraints. We investigated the effectiveness of an 'all-purpose' beam dump at E6 and the practicality of local muon shielding.